Tindakan Promotif Pengendalian Hipertensi pada Lansia sebagai Upaya Pencegahan Komplikasi - Gianevan, Nicholas Jirezra; Puspita, Hery Indria Dwi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Hypertension is a condition of high pressure in the blood vessels and is an incurable disease that requires lifelong treatment and good lifestyle modifications. The aim of this activity is to promote activities in the form of socialization on controlling hypertension in the elderly in Karangsari village especially improving the quality-of-life expectancy and reducing mortality due to hypertension complications in the elderly. The method used is starting with group gymnastics activities and continuing with socialization and finally a question-and-answer session from participants. analysis the area, socialization, and writing the report. The activity was attended by 80 participants. The results of this community service have a pivotal role and impactful because of the high enthusiasm of the elderly with many questions asked. The elderly are the age group that has the highest risk factors for hypertension, so disease control and medication compliance are the best ways to prevent complications of hypertension such as stroke, heart failure and myocardial infarction. The implication of this activity is assisting people, particularly elderly group to prevent from complications of hypertension earlier.